Structure, employment and productivity growth: evidence from the unorganised manufacturing sector in India, 1984/5-1994/5 / Rajesh Raj S N and Malathy Duraisamy (Faculty of Business and Management ; UiTM Press, 2005)
This paper analyses the structure, employment, and productivity growth in the unorganized manufacturing sector in India between 1984/5 and 1994/5 using National Sample Survey data for three periods, 1984-85, 1989-90 and 1994- 95. The size and structure of employment and manufacturing investment, and levels and changes in the partial factor productivity and capital intensity are examined at the two-digit industry level. A simple Cobb-Douglas production function is employed to analyze the output elasticity of labour and capital.